Martyrdom in the modern Middle East - Dehghani, Sasha; Horsch, Silvia (Ex oriente lux, 2014)
Continuity and transformation : martrydom in the Bahā'ī faith. The birth of a monotheistic religion in modernity : on jihad and martyrdom in the Bahā'ī Faith$hSasha Dehghani. Martrydom and servanthood in the Bābī and Bahā'ī faiths : a struggle to defend a cosmic order / Per-Olof Åkerdahl. Between Karbalā' and Tabriz : contested martyrdom narratives / Moojan MomenWitnessing and sacrifice : theological and philosophical implications of martyrdom. Sunni and Shiite passion stories revisited : on the superseding of sacrifice and its eventual re-empowerment / Angelika Neuwirth. Martyrium als Zeugnis : zur Frage nach der theologischen und politischen Valenz religiöser Zeugenschaft, dargelegt am Beispiel des Martyriums der Trappistenmönche von Tibhirine/Algerien / Joachim Negel. Gandhi and the sovereignty of death / Faisal Devji